Econometric Spatial Modeling to Analyze Interregional Development Inequality in Indonesia - Annisa Annisa (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study aims to analyze the development inequality between regions in Indonesia using a qualitative approach and econometric spatial modeling. Development inequality between the western and eastern regions of Indonesia, particularly in Java, Sumatra, and Papua, remains a significant issue that hinders equitable development. Based on interviews with local government officials, economic institutions, and communities, as well as data analysis from questionnaires and field observations, it was found that limited infrastructure, centralized development policies, and dependence on the natural resources sector are the primary factors contributing to inequality. Additionally, uneven investment allocation exacerbates regional inequality. The study also applied econometric spatial modeling to identify patterns of inequality and the impact of inter-regional interactions, suggesting that inequality in one region can affect inequality in another. These findings suggest that development policies should be more decentralized and tailored to local needs to achieve more effective and equitable development. The results of this study provide policymakers with recommendations for designing a more inclusive and equitable development strategy throughout Indonesia.